Safety verification method and selection method for ion implantation process photoresist layer thickness
Patent Information
- Application Number
- CN202611022452.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-10
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-07-10
AI Technical Summary
这时,光学测量系统的本底噪声可能会掩盖这些信号,因此,在评估低穿透率时往往无法提供可靠的定量数据,存在检测盲区
(1)提升了光阻层厚度验证的真实性与可靠性。本申请测量待测衬底表面离子含量的步骤不依赖于光学测量设备,因此不需要为了提高光学信号而提高注入剂量,能够采用与目标生产工艺一致的目标工艺剂量。由于验证条件与生产条件相匹配,所获得的判断结果能够直接反映光阻层在真实生产环境下的阻挡性能,从而避免了现有技术中因剂量不一致而导致的判定偏差,使得工艺开发与监控更为精准,能够为产线选定最优化的光阻层工艺参数,从而降低生产成本、提升工艺效率。
Smart Images

Figure CN122535230B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of semiconductor fabrication technology, and in particular to a method for verifying and selecting the thickness of photoresist layers in an ion implantation process. Background Technology
[0002] When evaluating the blocking ability of a photoresist layer during ion implantation, indirect methods based on optical thin-film measurements are typically employed. For example, in a typical approach, a photoresist layer of a specific thickness is formed on the substrate under test (SUT), and this layer is removed after ion implantation. The optical properties of the SUT surface are then measured using optical measurement equipment (e.g., an ellipsometer), and compared with measurements taken before implantation. If implanted ions penetrate the photoresist layer and enter the SUT, they can induce lattice damage or even amorphization in the near-surface region of the SUT. These physical changes are sufficient to alter the optical behavior of the region, resulting in an anomalous shift in the equivalent thickness value read from the optical measurements relative to the pre-implantation reference value.
[0003] However, this testing method has significant limitations in practical applications. For example, when the number of penetrating ions is small, the resulting changes in the optical signal may be very weak. In this case, the background noise of the optical measurement system may mask these signals, thus often failing to provide reliable quantitative data when assessing low transmittance, resulting in a detection blind zone. Furthermore, to ensure the optical signal reaches a detectable level, the aforementioned verification method typically requires a pre-set fixed injection dose. While this ensures that the instrument's detectable threshold is met, it causes the verification conditions to deviate from the actual process environment. This may lead to two consequences: first, photoresist that would be safe to use at actual lower doses may be misjudged as unqualified; second, low-level penetration existing at actual doses may not be correctly identified due to the fixed dose setting in the test. Therefore, due to inherent sensitivity limitations and distorted verification conditions, existing methods ultimately result in low accuracy and insufficient reference value in the detection results. Summary of the Invention
[0004] To solve the above-mentioned technical problems, one technical solution adopted by the present invention is to provide a safety verification method and selection method for the thickness of photoresist layer in ion implantation process. This method can achieve verification conditions that match the actual production process dosage in the safety verification of photoresist layer in ion implantation process, and can still obtain reliable quantitative detection data even when the ion penetration rate is low, thereby accurately determining whether the photoresist layer has been penetrated.
[0005] To achieve the above objectives, this invention provides a safety verification method for the thickness of photoresist layers in an ion implantation process, which can improve the authenticity and reliability of photoresist layer thickness verification, comprising the following steps: Take a substrate to be tested and perform an amorphization treatment on the surface of the substrate; A photoresist layer with a thickness to be verified is formed on the surface of the substrate to be tested. Perform ion implantation with the target process dose; Remove the photoresist layer from the surface of the substrate to be tested; The ion content on the surface of the substrate to be tested is measured, and the photoresist layer of the thickness to be verified is determined based on the ion content to determine whether it is penetrated under the target process dose.
[0006] Furthermore, in the step of performing amorphization treatment on the surface of the substrate to be tested, the surface of the substrate to be tested is amorphized using an amorphization ion implantation method.
[0007] Furthermore, in the step of performing amorphization treatment on the surface of the substrate to be tested, amorphization ion implantation is performed using Ge, C, and N2 via a Co-IMP process.
[0008] Furthermore, the step of measuring the ion content on the surface of the substrate to be tested includes the following sub-steps: A sacrificial layer is formed on the surface of the substrate to be tested after the photoresist layer is removed; The sacrificial layer is completely or partially removed from the surface of the substrate under test, and the sacrificial layer is collected. The ion content in the collected sacrificial layer is analyzed and used as the ion content on the surface of the substrate to be tested.
[0009] Furthermore, the sacrificial layer is configured as an oxide layer, which is formed on the surface of the substrate under test after the photoresist layer has been removed by an oxidation process.
[0010] Furthermore, the oxidation process includes dynamic post-oxidation process, plasma oxidation process, or thermal oxidation process.
[0011] Furthermore, in the step of completely or partially removing the sacrificial layer from the surface of the substrate under test: The sacrificial layer is removed by chemical etching or physical removal processes; The chemical etching includes wet etching or dry etching; The wet etching includes etching using hydrofluoric acid solution or hydrofluoric acid vapor.
[0012] Furthermore, in the step of analyzing the ion content in the collected sacrificial layer, mass spectrometry is used to analyze the ion content in the collected material, wherein the mass spectrometry is configured as inductively coupled plasma mass spectrometry.
[0013] Furthermore, in the step of completely or partially removing the sacrificial layer from the surface of the substrate under test and collecting the sacrificial layer, the oxide layer on the surface of the substrate under test is removed by etching with hydrofluoric acid vapor in a closed reaction chamber, and the droplets formed on the surface of the substrate under test are collected after etching is completed.
[0014] To solve the above-mentioned technical problems, another technical solution adopted by the present invention is: to provide a method for selecting the thickness of the photoresist layer in an ion implantation process, comprising the following steps: Multiple substrates to be tested are provided, and the surfaces of the multiple substrates to be tested are respectively subjected to amorphization treatment; Photoresist layers of different thicknesses are formed on the surfaces of the plurality of substrates to be tested, in order to cover the thickness range that needs to be verified; According to the dosage requirements of the ion implantation process, ion implantation with the same target process dosage is performed on the multiple substrates to be tested; Remove the photoresist layer from the surface of each substrate to be tested; The ion content on the surface of each substrate was measured separately. The photoresist layer thickness corresponding to the substrate under test with an ion content less than a preset threshold is determined as the photoresist layer thickness that has passed safety verification; and the minimum value among the photoresist layer thicknesses that have passed safety verification is selected as the photoresist layer thickness of this ion implantation process.
[0015] In summary, the safety verification method for the photoresist layer thickness in the ion implantation process of this application has the following unexpected technical effects: (1) Improved the authenticity and reliability of photoresist layer thickness verification. The step of measuring the ion content on the surface of the substrate under test in this application does not depend on optical measurement equipment. Therefore, it is not necessary to increase the injection dose in order to improve the optical signal, and the target process dose consistent with the target production process can be used. Since the verification conditions match the production conditions, the obtained judgment results can directly reflect the blocking performance of the photoresist layer in the real production environment, thereby avoiding the judgment deviation caused by inconsistent doses in the prior art. This makes process development and monitoring more accurate, and can select the optimal photoresist layer process parameters for the production line, thereby reducing production costs and improving process efficiency.
[0016] (2) In this application, the substrate to be tested is amorphized before ion implantation. The resulting amorphous layer can effectively suppress the channeling effect of subsequently implanted ions in the substrate, so that all ions that penetrate the photoresist are captured and uniformly distributed in a thin layer on the surface of the substrate. Based on this, the ion content on the surface of the substrate can be directly measured by high-sensitivity chemical analysis instead of relying on changes in optical signals. When amorphization treatment and chemical analysis are combined, the former fixes the penetrating ions in the thin layer on the surface, while the latter performs atomic-level quantification of the ions in the thin layer. Even if the ion penetration rate is as low as 0.01% or lower, quantitative detection can still be achieved. Thus, accurate process safety margins can be set based on accurate quantitative data rather than fuzzy noise signals, which can significantly improve the reliability and yield of the final device.
[0017] (3) This application provides a physically consistent and isotropic starting surface for each verification experiment through amorphization treatment, eliminating measurement fluctuations caused by the anisotropy of single-crystal silicon. Simultaneously, the ion content obtained using the sacrificial layer trapping and chemical analysis methods represents the absolute number of elements, rather than a physical quantity indirectly derived through optical models, thus ensuring high accuracy of the measurement results. Based on this, the selection method provides a quantifiable process judgment standard based on objective data by setting preset thresholds and selecting a minimum safe thickness. This effect stems from the standardization characteristics of amorphization treatment and the absolute quantitative characteristics of chemical analysis methods.
[0018] In summary, the verification and selection methods provided by this invention can provide reliable quantitative data in low-penetration scenarios under dosage conditions that match the actual production process, and provide an objective basis for the precise setting of process parameters.
[0019] This makes the verification results from different batches and different laboratories highly comparable and reproducible. In addition, chemical analysis methods obtain the absolute quantity of elements, rather than indirect changes in physical quantities, resulting in highly accurate test results. This allows for the setting of clear and unambiguous process qualification standards, making process decisions more scientific and reliable. Attached Figure Description
[0020] The accompanying drawings, which are included to provide a further understanding of the invention and form part of this invention, illustrate exemplary embodiments of the invention and are used to explain the invention, but do not constitute an undue limitation of the invention. In the drawings: Figure 1 This is a process flow diagram of a conventional photoresist layer verification method.
[0021] Figure 2 This is a process flow diagram of the safety verification method for the photoresist layer thickness in the ion implantation process of the present invention.
[0022] Figure 3 This is a schematic diagram of the surface of the substrate under test after amorphization treatment.
[0023] Figure 4 This is a schematic diagram after a photoresist layer has been formed on the surface of the substrate to be tested.
[0024] Figure 5 This is a schematic diagram of ion implantation.
[0025] Figure 6 This is a schematic diagram after the photoresist layer on the surface of the substrate under test has been removed.
[0026] Figure 7 This is a process flow diagram for measuring the ion content on the surface of a substrate using the VPD method.
[0027] Figure 8 This is a schematic diagram after a sacrificial layer has been formed on the surface of the substrate to be tested.
[0028] Figure 9 This is a schematic diagram after the sacrificial layer has been removed from the surface of the substrate under test.
[0029] Figure 10 This is a process flow diagram of an embodiment of the method for selecting the thickness of the photoresist layer in the ion implantation process of the present invention.
[0030] Figure 11 This is a process flow diagram for measuring the ion content on the surface of the substrate to be tested.
[0031] Figure 12 This is a bar chart of data obtained from photoresist verification measurements using a TW instrument.
[0032] Figure 13 This is a bar chart of data measured using the method described in this embodiment.
[0033] The diagrams in the instruction manual are labeled as follows: Substrate to be tested 1; Amorphous layer 2; Photoresist layer 3; Oxide layer 4. Detailed Implementation
[0034] The following disclosure provides various embodiments or examples for implementing different features of the invention. Specific examples of components and arrangements will be described below to simplify the invention. Of course, these are merely examples and are not intended to limit the invention. For example, in the following description, forming a first component above or on a second component may include embodiments where the first and second components are in direct contact, or embodiments where other components may be formed between the first and second components such that the first and second components are not in direct contact. Furthermore, reference numerals and / or characters may be repeated in various instances of the invention. Such repetition is for simplification and clarity and does not in itself indicate a relationship between the various embodiments and / or configurations.
[0035] Furthermore, spatial relation terms such as "below," "under," "below," "above," and "above" may be used herein to readily describe the relationship between one element or component and another element (or component) or component (or component) as shown in the figure. In addition to the orientations shown in the figure, spatial relation terms will encompass various different orientations of the device in use or operation. The device may be positioned in other ways (rotated 90 degrees or in other orientations), and will be interpreted accordingly through the spatial relation descriptors used herein.
[0036] Although the numerical ranges and parameter settings presented in this invention are approximations, the numerical settings in specific instances are reported as precisely as possible. Any numerical value, however, inherently contains certain inevitable errors arising from the standard deviation found in the respective test measurements. Similarly, as used herein, the term "about" generally refers to within 10%, 5%, 1%, or 0.5% of a given value or range. Alternatively, the term "about" means within an acceptable average standard error that can be conceived by one of ordinary skill in the art. Except in instances of operation / work, or unless expressly stated otherwise, all numerical ranges, totals, values, and percentages, such as those for material quantities, durations, temperatures, operating conditions, amounts, and other similarities disclosed herein, should be understood to be modified by the term "about" in all cases. Therefore, unless otherwise stated, the numerical parameter settings set forth in this invention and the appended claims are approximations that can be changed upon request. At a minimum, each numerical parameter should be interpreted based on the number of significant figures reported and the application of ordinary rounding techniques. A range herein may be expressed as from one endpoint to another or between two endpoints. All scopes disclosed herein include endpoints unless otherwise stated.
[0037] The following embodiments illustrate preferred embodiments of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the scope of protection of the present invention. Therefore, the scope of protection of this invention should be determined by the appended claims.
[0038] To facilitate understanding of the technical problem this invention aims to solve, a conventional method for verifying photoresist layer 3 is described below as an example. Please refer to... Figure 1 The conventional verification method for this type of photoresist layer 3 generally includes the following steps: S910. Take one substrate from the same batch as a reference substrate, which is not subjected to IMP (Ion Implantation).
[0039] S920. Take another substrate from the same batch as the substrate to be tested 1.
[0040] S930. Using a TW (Thin Film Wafer / Thickness of Wafer) instrument, perform preliminary thickness measurements on the reference substrate and another substrate 1 to be tested. If the thickness difference between the two is less than a preset difference threshold (e.g., the difference threshold can be 20 Å), continue the process. If the initial thickness difference between the reference substrate and the substrate 1 to be tested is greater than the difference threshold, it indicates that the uniformity of the batch of substrate 1 to be tested is very poor, and it is no longer meaningful to continue testing. It is necessary to take substrate 1 to be tested again.
[0041] S940, the following process steps are performed sequentially on the surface of the substrate 1 to be tested: deposition of photoresist layer 3, ion implantation, and removal of photoresist layer 3. Because the detection limit of the TW machine used in existing photoresist layer 3 verification methods is approximately 10... 11 atoms / cm 2 Therefore, the dose set for IMP is usually fixed at a relatively high value (typically 5 × 10⁻⁶). 13 ~1×10 14 ions / cm 2 The transmittance is less than 0.2%, meaning that less than 0.2% of the implanted material passes through the film, which still allows for measurable optical changes. When the penetration of implanted ions is below the detection limit of the instrument, the measurement signal may be submerged in the background noise of the equipment, blurring the boundary between signal and noise, and making the measured value significantly affected by noise.
[0042] After ion implantation, a post-implantation thickness measurement is performed using a TW instrument. This measurement measures the substrate thickness after removing photoresist layer 3. If the thickness of photoresist layer 3 is sufficient to block ions, the substrate is unaffected by ion implantation, and the thickness change measured by the TW instrument will be small. Conversely, if the thickness of photoresist layer 3 is insufficient, high-energy ions can penetrate it and enter the silicon lattice, causing amorphization or defects on the substrate surface. This alters the optical constants of the substrate surface, resulting in a significant shift in the thickness measured by the TW instrument.
[0043] Using the above method, corresponding to the detection limit of the TW machine, the dose set for IMP is usually fixed at a relatively high value (e.g., 5 × 10⁻⁶). 13 ~1×10 14 ions / cm 2The detection dose is a fixed value (between two values), which cannot guarantee that the detected dose is consistent with the actual dose of the ion implantation process. More importantly, the accuracy of the detection is limited by the detection limit of the TW instrument. When the penetration is less than the detection limit of the TW instrument, the signal measured by the TW instrument may be submerged in the background noise of the equipment. Based on the test data, it is impossible to determine whether it is real ion penetration, instrument vibration, or environmental interference. Therefore, it is impossible to accurately verify whether the thickness of photoresist layer 3 is absolutely safe, resulting in low accuracy of the detection results.
[0044] Please see Figure 2 , Figure 2 A process flow diagram of a method for verifying the safety of photoresist layer thickness in an ion implantation process is shown. In the illustrated embodiment, the method for verifying the safety of photoresist layer thickness in an ion implantation process includes the following steps: S110, please refer to Figure 3 A substrate 1 to be tested is taken, and its surface is subjected to amorphization treatment. The amorphization treatment of the surface of the substrate 1 is achieved by injecting external energy into the surface of crystalline silicon to introduce controllable, high-density lattice defects, thereby temporarily destroying its perfect periodic long-range ordered structure at the atomic scale and forming an amorphous layer 2 of predetermined thickness and properties.
[0045] The term "substrate under test 1" generally refers to any support structure on which ion implantation is performed. In one or more embodiments, the substrate under test 1 can be a single-crystal silicon wafer with a crystal orientation of (100), (110), or (111), a doping type of p-type or n-type, and a resistivity that can vary within a certain range according to device requirements. In one or more embodiments, the substrate under test 1 can also be a silicon-on-insulator substrate, or include, but is not limited to, silicon-germanium (SiGe), germanium (Ge), III-V compound semiconductors (such as gallium arsenide, indium phosphide, gallium nitride), II-VI compound semiconductors (such as cadmium telluride, zinc selenide), and wide bandgap materials such as silicon carbide (SiC) or sapphire.
[0046] In one or more embodiments, one or more dielectric films (e.g., silicon oxide, silicon nitride, high-k materials) or conductive films (e.g., metal silicides, polycrystalline silicon) may be pre-formed on the surface of the substrate 1 under test, as long as the target area for subsequent ion implantation is located below the photoresist layer 3, within the substrate 1 under test, or within a functional layer thereon. Before amorphization, the substrate 1 under test is typically subjected to wet chemical cleaning (e.g., RCA standard cleaning) or in-situ plasma cleaning to remove surface contaminants and native oxides, thereby ensuring the uniformity and repeatability of amorphization ion implantation.
[0047] In one or more embodiments, the substrate 1 under test may already contain a patterned structure, such as shallow trench isolation, gate structure, silicon fins in a fin field-effect transistor, embedded source / drain regions, or buried layers. For such substrates 1 under test with pre-existing topological morphology, the coverage capability of the photoresist layer 3 and the penetration behavior of implanted ions may be affected by the pattern density and morphology. Therefore, this verification method is also applicable to evaluating the photoresist safety on substrates 1 under test with these patterned structures. Before amorphization, the substrate 1 under test is typically subjected to wet chemical cleaning (e.g., RCA standard cleaning) or in-situ plasma cleaning to remove surface contaminants and native oxides, thereby ensuring the uniformity and repeatability of amorphization ion implantation.
[0048] In one or more embodiments, the purpose of the amorphization process is to introduce a high density of lattice defects in the near-surface region of crystalline silicon (or more generally, the crystal structure of the substrate material) to disrupt its periodic long-range ordered structure and form an amorphous layer 2 of a predetermined thickness (e.g., about 20 nm to 50 nm).
[0049] In one or more embodiments, the surface of the substrate 1 to be tested can be amorphized using an amorphous ion implantation method. Preferably, the surface of the substrate 1 to be tested is amorphized using Ge, C, and N2 through a Co-IMP (Co-Implantation) process. The principle is as follows: The process of ion implantation amorphization is a collisional cascade. When high-energy ions (such as Ge+) are incident into a single-crystal silicon target, they undergo violent Coulomb collisions with silicon atomic nuclei, transferring energy to primary ejected atoms. These primary ejected atoms then undergo secondary and tertiary collisions with other lattice atoms, forming a complex collisional cascade. When the density of Frenkel defect pairs (vacancy-interstitial atom pairs) generated per unit volume in the implanted region exceeds a certain critical threshold, the local long-range ordered structure cannot be maintained, the lattice collapses, and a continuous amorphous layer is formed.
[0050] In this process, Ge+ (germanium ions) are highly efficient physical disruptors. Because germanium has a much larger atomic mass than silicon, it possesses a mass advantage. According to classical collision theory, the energy transfer efficiency during a collision is directly related to the mass ratio of the two particles; the larger incident ion can transfer more kinetic energy to the target atom, resulting in a more intense and denser collision cascade. This makes Ge+ highly efficient at inducing damage when forming amorphous layers, several times, even more than ten times, that of silicon through self-ion implantation.
[0051] Furthermore, Ge+ offers advantages in both dosage and depth. Using Ge+ allows for the rapid formation of uniformly thick amorphous layers at relatively low implantation doses. This not only improves process efficiency but also reduces other complex defects that might be introduced by excessively high implantation doses. Simultaneously, the relatively shallow projection range of Ge+ facilitates precise control over the initiation position and thickness of the amorphous layer, which is crucial for subsequent ultra-shallow junction formation.
[0052] If only Ge+ is implanted, the resulting amorphous layer is metastable. During subsequent heat treatment, this amorphous layer will undergo solid-phase epitaxial regrowth from the intact crystal at the bottom of the substrate 1, with the amorphous / crystalline interface rapidly advancing towards the surface until the entire amorphous layer reverts to a crystalline state. This process affects impurity distribution and device performance. By introducing carbon and nitrogen, this regrowth process can be suppressed; C+ (carbon ions) and N2+ (nitrogen ions) can act as precise chemical stabilizers in the process.
[0053] Using Ge / C / N2 combination for ion implantation has the following advantages: First, it can suppress transient enhanced diffusion and recrystallization. Carbon atoms mainly occupy interstitial sites in the silicon lattice. During the annealing process after the formation of the amorphous layer, the abundant carbon interstitial atoms can effectively capture silicon interstitial atoms. Silicon interstitial atoms are the main carriers driving the solid-phase epitaxial regrowth of the amorphous layer and the transient enhanced diffusion of impurities such as B and P. By being captured by C atoms, the concentration and mobility of silicon interstitial atoms are greatly reduced, thereby freezing the regrowth interface and keeping the amorphous layer stable in subsequent processes. At the same time, the recrystallization of interstitial sites can also reduce residual defects.
[0054] Secondly, it possesses interface pinning and impurity segregation control functions. Nitrogen atoms are highly reactive; during amorphization, they tend to aggregate near the amorphous / crystalline interface and form strong covalent Si-N bonds with silicon. This nitrogen-rich interface layer is thermodynamically very stable, acting as a chemical anchor to pin the amorphous / crystalline interface and slow down the regrowth rate. Furthermore, nitrogen can form stable compounds with certain metallic impurities (such as Cu), acting as a getter and preventing impurities from diffusing into the active region.
[0055] Third, strain can be introduced to influence defect migration and bonding. Since the covalent radius of germanium atoms is larger than that of silicon atoms, while the covalent radius of carbon atoms is much smaller than that of silicon atoms, Ge / C co-implantation can locally introduce complex strain fields of tensile and compressive strain. This controlled strain can modulate the growth of subsequent epitaxial layers or improve carrier mobility through band engineering. Simultaneously, the strain field can also influence defect migration and bonding, promoting the formation of more stable defect complexes rather than harmful extended defects.
[0056] In this step, Ge / C / N2 is used to perform amorphization treatment on the surface of the substrate 1 under test through the Co-IMP process. This can build a stable, reliable, and highly sensitive detection reference platform, so that any ions that penetrate the photoresist layer 3 will be retained in the surface area without damage, thus ensuring the accuracy of subsequent measurements.
[0057] S120, please refer to Figure 4 A photoresist layer 3 with a thickness to be verified is formed on the surface of the substrate 1 to be tested.
[0058] The purpose of this step is to construct a photoresist layer 3 barrier with a uniform target thickness on the surface of the amorphized substrate 1. The photoresist layer 3 can be formed using a standard spin coating process. By precisely controlling the viscosity of the photoresist layer 3 adhesive, the spin coating speed, acceleration, and spin coating time, a highly uniform film can be obtained on the surface of the substrate 1. Afterward, a pre-baking step is performed to remove the solvent and stabilize the film thickness.
[0059] Photoresist layer 3 refers to any polymer material layer that can be formed on the surface of the substrate 1 under test by spin coating, spraying, or vapor deposition. Its main function is to act as a physical mask during ion implantation, selectively blocking dopants from entering the protected area below. The material of photoresist layer 3 can be selected from positive or negative photoresist. In positive photoresist, the exposed area dissolves in the developer, while the unexposed area remains; in negative photoresist, the opposite occurs. In deep submicron and advanced node processes, chemically amplified photoresist is commonly used, containing photoacid-generating agents that catalyze the deprotection reaction of the resin during post-exposure baking, thereby altering the solubility. CAR (Chemically Amplified Resist) is suitable for high-volume manufacturing environments due to its high photosensitivity. Photoresist layer 3 may also contain additives such as photosensitizers, crosslinking agents, surfactants, and light-absorbing dyes (used to control the standing wave effect during exposure). Photoresist layer 3 can be a single-layer structure or a multi-layer structure (e.g., containing a bottom anti-reflective coating BARC or a top protective coating).
[0060] The thickness of photoresist layer 3 depends on the energy and type of implanted ions and the required level of obstruction. In typical processes, the thickness of photoresist layer 3 can be selected in the range of approximately 1 μm to 10 μm. The formation process typically includes spin coating and soft baking steps. For example, the photoresist material is spread on the wafer surface at a predetermined rotation speed (e.g., 2000 rpm to 4000 rpm) for approximately 30 to 60 seconds, followed by soft baking on a hot plate at approximately 90°C to 130°C to remove the solvent. Different film thicknesses can be obtained by adjusting the viscosity of the photoresist and the spin coating speed. For instance, if the target process requires a 3.6 μm thick photoresist layer 3 during ion implantation, the film thickness formed in this step should be approximately 3.6 μm. After coating, the film thickness can be measured at multiple locations (e.g., center, radius, edge) on the substrate 1 using a separate film thickness measurement device (e.g., ellipsometry or reflectance spectrometer) to ensure that the deviation between the actual film thickness and the target value is within the allowable tolerance range (e.g., ±2%).
[0061] S130, please refer to Figure 5 Perform ion implantation with the target process dose.
[0062] Unlike conventional verification methods that use a fixed high dose to accommodate optical detection methods, this step simulates the real ion implantation process environment. That is, it directly uses the implantation dose specified in the ion implantation process to be verified to conduct experiments, so that the verification results have high reference value for the ion implantation process.
[0063] The traditional verification methods used in existing technologies, which rely on optical measurement equipment (such as the TW instrument), have limitations due to the detection limits of these devices. To avoid the signal falling below the detection limit, a fixed high dose (typically 5 × 10⁻⁶) must be used regardless of the actual process dose of the ion implantation process. 13 ~1×10 14 ions / cm 2 Injecting a fixed value (between a certain range) results in verification conditions that do not match actual production conditions, making it a compromise testing scheme that sacrifices realism.
[0064] This embodiment completely eliminates the reliance on the sensitivity limits of optical measurement equipment by employing ultra-high sensitivity direct ion content measurement technology in subsequent steps instead of optical measurement equipment for ion detection. Therefore, the target dose from the production line process card can be directly used for implantation. For example, in the ion implantation process requiring verification, the ion implantation dose is 2 × 10⁻⁶. 13 ions / cm 2 When the target process dosage is 2×10, the target process dosage is 2×10. 13 ions / cm 2 In this step, 2×1013 ions / cm 2 The substrate 1 to be tested is implanted with an ion implantation dose of [amount missing]. It can be seen that by adopting the method of this embodiment, the existing technology, which is limited by the detection sensitivity of the equipment, requires a fixed high dose for ion implantation regardless of the required dose for the ion implantation process. This solves the problem of the experimental dose not matching the verification requirements in the existing technology.
[0065] Ion implantation dose is a primary parameter determining the electrical characteristics of devices, such as junction depth and doping concentration. This step ensures that the experimental dose is strictly consistent with the target dose, meaning that the penetration phenomenon observed in the experiment occurs under physically identical conditions to those encountered in actual processes. This leads to more accurate conclusions regarding the adequacy of the photoresist layer 3 thickness. Of course, in addition to the ion implantation dose, all other process parameters, such as the type of ion implantation, energy, implantation angle, and wafer temperature, must also be completely consistent with the ion implantation process parameters to be verified. Only in this way can we ensure that the distribution, scattering, and energy loss mechanisms of ions in the photoresist and the substrate under test are exactly the same as in production, thus ensuring a high degree of consistency between the experimental results of penetration behavior and actual conditions.
[0066] S140, please refer to Figure 6 The photoresist layer 3 on the surface of the substrate 1 to be tested is removed. After ion implantation, the photoresist layer 3 needs to be completely and thoroughly removed from the surface of the substrate 1 to be tested. The photoresist layer 3 can be removed by wet chemical stripping, dry ashing, or a combination of both.
[0067] When removing photoresist layer 3 using dry ashing, oxygen plasma ashing is typically employed. The principle is that the oxygen plasma reacts with the photoresist layer 3 to generate volatile gases such as CO2 and H2O, which are then removed. Its advantages include no chemical etching of the underlying layer of the substrate 1 and thorough removal. However, careful control of the plasma power and duration is necessary to avoid excessive oxidation or heating that could affect the amorphous silicon surface. The completeness of photoresist removal can be determined by monitoring changes in the intensity of spectral lines at specific wavelengths using optical emission spectroscopy.
[0068] When removing photoresist layer 3 using wet chemical stripping, organic solvents (such as acetone, N-methylpyrrolidone) or specialized alkaline / acidic stripping solutions can be used. The photoresist layer 3 is stripped from the substrate 1 through dissolution or swelling. This method has low temperature sensitivity, but it is necessary to ensure that the stripping solution is compatible with the substrate 1 and does not corrode the silicon surface. Afterwards, thorough cleaning is required to remove organic residues and ensure that the surface of the substrate 1 is clean and chemically stable.
[0069] For photoresist that may harden after ion implantation, a combination of "dry + wet" methods can be used. The polymer structure of the photoresist layer 3 can be broken down by oxygen plasma under moderate conditions to make it loose, and then the residue can be removed by wet chemical stripping. This can balance the removal efficiency and the cleanliness of the surface of the substrate 1 under test.
[0070] After ion implantation, the photoresist layer 3 must be completely removed without interfering with the surface state of the implanted substrate 1. This step is a prerequisite for subsequent accurate measurement of surface ion content, requiring complete removal of the photoresist layer 3 without introducing contamination or altering the surface morphology and chemical state of the substrate 1. Afterward, the surface roughness or water contact angle of the substrate 1 after photoresist layer 3 removal can be quickly measured and compared with an uncoated reference sheet to confirm that the photoresist removal process did not cause physical damage to the surface of the substrate 1 or introduce hydrophobic / hydrophilic contamination.
[0071] S150. Measure the ion content on the surface of the substrate 1 to be tested, and determine whether the photoresist layer 3 of the thickness to be verified is penetrated under the target process dose based on the ion content.
[0072] In this step, the ion content on the surface of the substrate 1 can be measured using the VPD (Vapor Phase Decomposition) method.
[0073] Please see Figure 7 For example, this step may include the following sub-steps: S151, please refer to Figure 8 A sacrificial layer is formed on the surface of the substrate 1 to be tested after the photoresist layer 3 is removed.
[0074] In this embodiment, the sacrificial layer can be configured as an oxide layer 4, which can be formed on the surface of the substrate 1 to be tested after the photoresist layer 3 has been removed by an oxidation process.
[0075] The oxidation process may include DPO (Dynamic Post-Oxidation), plasma oxidation, or thermal oxidation. In this embodiment, DPO is preferably used to oxidize the surface of the substrate 1 under test, thereby forming an oxide layer 4 on the surface of the substrate 1 under test. DPO is a plasma oxidation process performed at or near room temperature, mainly used to grow an ultrathin, dense oxide layer 4 with very low interface states on the silicon surface.
[0076] The DPO process utilizes oxygen plasma to directly react with silicon to generate an ultrathin (e.g., 2nm to 10nm) and dense SiO2 layer. During this process, the substrate 1 is not subjected to high temperatures, thus preventing the regrowth of the amorphous layer and potential ion diffusion. The generated oxide layer 4 acts as a trapping layer, capable of binding ions that originally penetrated the photoresist and remained on the silicon surface (or near the surface amorphous layer) into the oxide layer 4 or adsorbing them at the oxide layer 4 / silicon interface.
[0077] S152, please see Figure 9 The sacrificial layer is completely or partially removed from the surface of the substrate 1 under test, and the sacrificial layer is collected.
[0078] In one or more embodiments, the sacrificial layer can be removed by chemical etching or physical removal processes. When the sacrificial layer is removed by chemical etching, wet etching or dry etching can be used. When wet etching is used, hydrofluoric acid solution or hydrofluoric acid vapor can be used for etching.
[0079] In one or more embodiments, the oxide layer 4 on the surface of the substrate 1 under test is preferably removed by etching with hydrofluoric acid vapor in a sealed reaction chamber, and the droplets formed on the surface of the substrate 1 under test are collected after etching. Specifically, the substrate 1 under test is placed in a sealed reaction chamber with a heated HF (hydrofluoric acid) source or an HF / H2O mixed vapor source below or around it; the HF vapor is uniformly filled into the reaction chamber to react with the SiO2 on the surface of the substrate 1 under test. The substrate 1 under test can also be rotated or the nozzle moved to ensure that the entire surface of the substrate 1 under test is scanned. During this process, the solid SiO2 reacts with the HF vapor to generate a liquid fluorosilicic acid solution, which releases the metal ions originally locked in the oxide layer 4 into this small droplet of liquid. The droplets on the surface of the substrate 1 under test are then collected, and the solution containing all dissolved metal is completely collected for subsequent ion content detection. Because the oxide layer 4 formed by DPO is uniform and dense, it can ensure uniform etching of HF vapor and completely release the adsorbed ions into the droplets for subsequent detection, thereby improving measurement sensitivity and accuracy.
[0080] If other etching methods are used, and conventional detection methods are employed to directly clean the substrate 1 with liquid, the volume of the cleaning solution may reach the level of 100 mL, resulting in a very low ion concentration in the solution and making detection difficult. However, when using the VPD method for detection, the volume of the liquid obtained from the reaction of HF vapor with the oxide layer 4 may only be on the level of 100 µL. Compared with conventional methods, the ion concentration in the solution is increased by approximately 1000 times, which can significantly improve the detection limit of subsequent ICP-MS (Inductively Coupled Plasma Mass Spectrometry).
[0081] S153. Analyze the ion content in the collected sacrificial layer as the ion content on the surface of the substrate 1 to be tested.
[0082] In one or more embodiments, mass spectrometry is used to analyze the ion content in the collected substance. For example, the ion content in the collected substance (i.e., droplets) can be detected by ICP-MS. The general principle is as follows: the sample (such as the collected droplets) is introduced into a high-temperature plasma of approximately 7000–10000 K. The sample is evaporated, atomized, and ionized into single-charged positive ions. These ions enter the mass spectrometer through an interface and are separated according to their mass-to-charge ratio (m / z) in a quadrupole or time-of-flight mass analyzer, and counted by devices such as electron multiplier tubes. ICP-MS can separate different elements in the sample by weight and count the specific number of each type, thereby accurately quantifying the number of ions and solving the problem of limited detection accuracy when using TW instruments.
[0083] In summary, the safety verification method for photoresist thickness in the ion implantation process of this application has the following unexpected technical effects: (1) Improved the authenticity and reliability of photoresist layer 3 thickness verification. Addressing the dose distortion problem caused by the detection limitations of optical measurement equipment in existing technologies, this application improves the detection method, eliminating the influence of optical measurement equipment and using an ion implantation dose completely consistent with the target production process for verification. This dose-consistent verification method ensures that the verification experiment conditions are an accurate mirror image of the actual process conditions. The results obtained directly and accurately reflect the blocking performance of the photoresist layer 3 thickness in real application scenarios, thus making the verification conclusions more accurate. Eliminating the risk of misjudgment due to verification condition distortion makes process development and monitoring more precise, avoids the selection of overly conservative photoresist layer 3 process parameters, and helps reduce production costs and improve process efficiency.
[0084] (2) This invention achieves precise quantitative detection of low transmittance, overcoming the measurement blind zone of traditional methods. Addressing the sensitivity limitations and data noise issues of existing optical measurement equipment, this application amorphizes the substrate 1 under test. The resulting amorphous layer effectively suppresses the channeling effect of subsequently implanted ions in silicon, ensuring that all ions penetrating the photoresist are captured and uniformly distributed within a thin layer on the surface of the substrate 1. This allows for direct chemical analysis to measure the ion content on the surface of the substrate 1. Through these improvements, ion transmittance of 0.01% or even lower can be accurately measured, eliminating the measurement blind zone of traditional methods in low transmittance regions and achieving high-precision monitoring of the blocking capability of the photoresist layer 3.
[0085] (3) Enhanced repeatability and accuracy of measurement data. Traditional measurement methods are easily affected by various factors such as the crystal orientation of the substrate 1, surface roughness, and ambient temperature and humidity, resulting in large fluctuations in measurement results. The lack of objective and unified quantitative standards may lead to inconsistencies in verification conclusions between different personnel and different batches, affecting process stability. This application provides a physically consistent and isotropic starting surface for each verification experiment through amorphization treatment, thereby eliminating measurement fluctuations caused by the anisotropy of single-crystal silicon; this makes the verification results of different batches and different laboratories comparable and repeatable. In addition, chemical analysis methods such as VPD and ICP-MS provide the quantity of elements rather than indirect changes in physical quantities, and their results are more accurate, thus allowing for the setting of clear and unambiguous process qualification standards.
[0086] The above method addresses the process of verifying the thickness of a single photoresist layer 3. In actual process development or monitoring, it is often necessary to determine the minimum safe thickness within a possible thickness range. Therefore, this invention also provides a method for selecting the thickness of the photoresist layer 3.
[0087] Please see Figure 10 , Figure 10 A process flow diagram of a method for selecting the thickness of a photoresist layer in an ion implantation process is shown. In the illustrated embodiment, the safety verification method for the thickness of the photoresist layer in the ion implantation process includes the following steps: S210. Provide a plurality of substrates 1 to be tested, and perform amorphization treatment on the surfaces of the plurality of substrates 1 to be tested respectively. In this step, the amorphization treatment of the surface of the substrates 1 to be tested can be performed by amorphization ion implantation, preferably by using Ge, C and N2 to perform amorphization treatment of the surface of the substrates 1 to be tested by Co-IMP process.
[0088] The purpose of the verification experiment was to detect trace ions penetrating the photoresist layer 3. In this step, the substrate 1 under test was amorphized using Ge / C / N2 via Co-IMP technology. This created a stable amorphous layer, providing an inert trap for penetrating ions, firmly fixing them near the surface and preventing them from penetrating deep into the substrate 1 within the lattice channels. This constructed a stable, reliable, and highly sensitive detection benchmark platform, ensuring the signal strength and accuracy of subsequent VPD or SIMS detection. Furthermore, the amorphous layer formed by co-implantation of Ge / C / N2 exhibits high thermal stability and minimal morphological changes during subsequent room-temperature oxidation steps. This ensures that the physicochemical state of the detection platform remains consistent across different batches of substrates 1 with varying photoresist layer 3 thicknesses, thus isolating variables in the amorphous layer 2, eliminating process-related interference, and allowing differences in measurement results to be entirely attributed to the photoresist layer 3 thickness and the implantation conditions themselves. Because the amorphous layer can effectively suppress the channeling effect and ion diffusion, the distribution of penetrating ions is more concentrated, increasing the ion concentration per unit area and indirectly improving the detection sensitivity of the analytical equipment, making it possible to accurately measure low penetration (e.g., <0.1%).
[0089] S220. Photoresist layers 3 of different thicknesses are formed on the surfaces of the plurality of substrates 1 to cover the thickness range to be verified. When it is necessary to find the critical photoresist layer 3 thickness under predetermined ion implantation process conditions within the range of 3.0 μm to 4.0 μm photoresist layer 3 thickness, photoresist layers 3 of different thicknesses within the range of 3.0 μm to 4.0 μm are grown on the surfaces of the plurality of substrates 1 to be tested. For example, thicknesses of 3.0 μm, 3.2 μm, 3.4 μm, 3.6 μm, 3.8 μm, and 4.0 μm can be grown on the surfaces of the six substrates 1 to be tested, respectively. Of course, in order to obtain a more accurate critical photoresist layer 3 thickness under the ion implantation process conditions, photoresist layers 3 of different thicknesses can also be grown on the surfaces of the eleven substrates 1 to be tested at intervals of 0.1 μm, thereby accurately defining the safe operating window of the ion implantation process and providing accurate safe photoresist layer 3 thickness data for the production line.
[0090] S230. Based on the dosage requirements of the ion implantation process, perform ion implantation with the same target process dosage on the plurality of test substrates 1. For example, when the ion implantation process to be verified has an ion implantation dosage of 2 × 10⁻⁶, 13 ions / cm 2 In this case, 2×10 can be directly used in this step. 13 ions / cm 2The ion implantation dose is applied to the substrate 1 under test. It can be seen that the method of this embodiment changes the situation in the prior art where, due to the limitation of the detection sensitivity of the equipment, a fixed high dose can only be used for ion implantation regardless of the required dose of the ion implantation process. This solves the problem of the experimental dose not matching the verification requirements in the prior art. In this step, multiple substrates 1 under test can be ion implanted in the same batch to ensure that the implantation dose of each substrate 1 is the same.
[0091] S240. Remove the photoresist layer 3 from the surface of each substrate 1 under test. After ion implantation, the photoresist layer 3 needs to be completely and thoroughly removed from the surface of the substrate 1 under test. This can be done using wet chemical stripping, plasma ashing, or a combination of both. Wet stripping primarily uses organic solvents or specialized stripping solutions to remove the photoresist layer 3 through dissolution or swelling.
[0092] S250, Measure the ion content on the surface of each substrate 1 to be tested.
[0093] For example, please see Figure 11 This step can use the VPD method to measure the ion content on the surface of each substrate 1 to be tested, and can specifically include the following sub-steps: S251. A sacrificial layer is formed on the surface of the substrate 1 to be tested after the photoresist layer 3 is removed.
[0094] In this embodiment, the sacrificial layer is preferably configured as an oxide layer 4, which is formed on the surface of the substrate 1 to be tested after the photoresist layer 3 has been removed by an oxidation process. The oxide layer 4 forms an ion trapping layer, chemically adsorbing ions that penetrate the photoresist layer 3 onto its surface, locking the penetrating ions, and preventing these ions from volatilizing or diffusing during subsequent processing.
[0095] The oxidation process can employ DPO, plasma oxidation, or thermal oxidation; in this embodiment, DPO is preferred. DPO uses plasma-enhanced oxidation, eliminating the need for high-temperature heating and thus achieving a very low thermal budget. In this step, each substrate 1 under test can be oxidized in the same environment to form the oxide layer 4.
[0096] S252. The sacrificial layer (i.e., oxide layer 4) is completely or partially removed from the surface of the substrate 1 under test, and the sacrificial layer is collected. In this embodiment, it is preferable to remove the oxide layer 4 on the surface of the substrate 1 under test by etching with hydrofluoric acid vapor in a closed reaction chamber, and collect the droplets formed on the surface of the substrate 1 under test after etching. Since the oxide layer 4 formed by DPO is uniform and dense, it can ensure uniform etching of HF vapor and completely release the adsorbed ions into the droplets for subsequent detection, thereby improving the measurement sensitivity and accuracy. The sacrificial layer needs to be removed from each substrate 1 under test individually.
[0097] S253. Analyze the ion content in the collected sacrificial layer as the ion content of the surface of the substrate 1 to be tested. In this step, it is preferable to use ICP-MS to analyze the ion content in the collected material. ICP-MS can separate different elements in the sample by weight and count the specific number of each type, thereby accurately quantifying the number of ions and solving the problem of limited detection accuracy when using TW equipment.
[0098] S260. The thickness of the photoresist layer 3 corresponding to the substrate 1 under test with an ion content less than a preset threshold is determined as the thickness of the photoresist layer 3 that has passed the safety verification; and the minimum value is selected from the thicknesses of the photoresist layer 3 that have passed the safety verification as the thickness of the photoresist layer 3 of the ion implantation process.
[0099] For example, please see Figure 12 The data is obtained from PR (photoresist) verification using the TW machine. Figure 12 The shaded areas marked "Safe" represent areas where ions did not penetrate as detected by the TW machine, while the shaded areas marked "Risk of Breakdown" represent areas where ions penetrated as detected by the TW machine. According to Figure 12 The data in the data can only determine that when the thickness of photoresist layer 3 is 3.2 μm, ions will penetrate photoresist layer 3, and when the thickness of photoresist layer 3 is 3.6 μm, ions will not penetrate. Therefore, it can be concluded that the thickness of photoresist layer 3 is 3.6 μm and it enters the safe zone.
[0100] For example, please see Figure 13 The data are obtained by testing using the method of this embodiment under the same ion implantation process conditions. Figure 13 The data shows that ions penetrated when the thickness of photoresist layer 3 was 3.0μm, 3.2μm, 3.4μm, and 3.6μm. No ion penetration was detected when the thickness of photoresist layer 3 was 3.8μm and 4.0μm. It can be seen that 3.6μm is not a safe thickness for photoresist layer 3. The safe zone is only entered when the thickness of photoresist layer 3 is 3.8μm. Figure 13The areas marked as safe for detection using the TW instrument are actually detected using the method described in this embodiment. This demonstrates that the test results using the TW instrument have a significant error. If the TW instrument measurement results are based on a 3.6 μm photoresist layer thickness, ion penetration will occur, leading to performance degradation or even damage to the device.
[0101] In summary, the method for selecting the photoresist layer thickness in the ion implantation process of this application has the following unexpected technical effects: (1) This application solves the problem of low accuracy in traditional methods. By combining the amorphization treatment of the substrate 1 under test with the synergistic effect of VPD and ICP-MS, this application can perform atomic-level precise quantification of trace ions on the surface, significantly improving the detection sensitivity by orders of magnitude. Even with a transmittance as low as 0.01%, accurate and quantitative data can be obtained, achieving full-range, blind-zone-free monitoring capability. The verification is performed using an ion implantation dose that is completely consistent with the target production line process, making the verification experiment a true mirror of the actual production environment. The results directly and accurately reflect the performance of the photoresist in the real application scenario, avoiding misjudgment due to distortion of verification conditions, and providing a reliable basis for the precise setting of process parameters.
[0102] (2) A complete process window calibration for the blocking performance of photoresist layer 3 was achieved. This application prepared a series of photoresist layers 3 with gradient thicknesses covering the verification range in parallel on the same batch of substrates 1 to be tested, and processed them under the same ion implantation conditions and measured them separately. This allowed for the acquisition of a complete data curve of ion penetration as a function of the thickness of photoresist layer 3. This data can intuitively and accurately reveal the critical safe thickness under a specific process dose, providing a precise basis for process setting.
[0103] (3) It provides valuable underlying data for process modeling and optimization. The highly sensitive and quantitative "thickness-penetration" relationship data obtained by the method of this application can be used as input for ion blocking models in calibration process simulation software. Through curve fitting, key physical parameters such as the blocking ability and range distribution of ions in a specific photoresist material can be deduced. This enables process development to shift from empirical trial and error to model prediction, and can accelerate the research and development process of new materials and new processes.
Claims
1. A method for verifying the safety of photoresist layer thickness in an ion implantation process, characterized in that, Includes the following steps: Take a substrate to be tested and perform an amorphization treatment on the surface of the substrate to form an amorphous layer on the surface of the substrate; the amorphous layer is used to suppress the channeling effect of injected ions penetrating the photoresist layer in the substrate to be tested, so that the injected ions penetrating the photoresist layer are captured and distributed in a thin layer on the surface of the substrate to be tested. A photoresist layer with a thickness to be verified is formed on the surface of the substrate to be tested. Perform ion implantation with a target process dose; wherein the target process dose is the implantation dose specified in the ion implantation process to be verified; Remove the photoresist layer from the surface of the substrate to be tested; The ion content on the surface of the substrate to be tested is measured, and the photoresist layer of the thickness to be verified is determined based on the ion content to determine whether it is penetrated under the target process dose. The step of measuring the ion content on the surface of the substrate to be tested includes the following sub-steps: A sacrificial layer is formed on the surface of the substrate under test after the photoresist layer is removed; the sacrificial layer is configured as an oxide layer, which is formed on the surface of the substrate under test after the photoresist layer is removed by an oxidation process, and forms an ion trapping layer through the oxide layer, chemically adsorbing ions that penetrate the photoresist layer on its surface; The sacrificial layer is completely or partially removed from the surface of the substrate under test and the sacrificial layer is collected. In this step, the oxide layer on the surface of the substrate under test is removed by etching with hydrofluoric acid vapor in a closed reaction chamber, and the droplets formed on the surface of the substrate under test are collected after the etching is completed. The ion content in the collected sacrificial layer was analyzed by inductively coupled plasma mass spectrometry and used as the ion content on the surface of the substrate to be tested.
2. The method for verifying the safety of photoresist layer thickness in ion implantation process according to claim 1, characterized in that: In the step of performing amorphization treatment on the surface of the substrate to be tested, the surface of the substrate to be tested is treated with amorphization ion implantation.
3. The method for verifying the safety of photoresist layer thickness in ion implantation process according to claim 2, characterized in that: In the step of amorphizing the surface of the substrate to be tested, amorphous ion implantation is performed using Ge, C and N2 via the Co-IMP process.
4. The method for verifying the safety of photoresist layer thickness in ion implantation process according to claim 1, characterized in that: The oxidation process includes dynamic post-oxidation process, plasma oxidation process, or thermal oxidation process.
5. A method for selecting the thickness of a photoresist layer in an ion implantation process, characterized in that, Includes the following steps: A plurality of substrates to be tested are provided, and the surfaces of the plurality of substrates to be tested are subjected to amorphization treatment to form an amorphous layer on the surfaces of the plurality of substrates to be tested. The amorphous layer is used to suppress the channeling effect of injected ions penetrating the photoresist layer in the substrate under test, thereby trapping the injected ions penetrating the photoresist layer and distributing them in a thin layer on the surface of the substrate under test. Photoresist layers of different thicknesses are formed on the surfaces of the plurality of substrates to be tested, in order to cover the thickness range that needs to be verified; According to the dosage requirements of the ion implantation process, ion implantation with the same target process dosage is performed on the multiple substrates to be tested; wherein, the target process dosage is the implantation dosage specified in the ion implantation process for the selected photoresist layer thickness; Remove the photoresist layer from the surface of each substrate to be tested; The ion content on the surface of each substrate was measured separately. The photoresist layer thickness corresponding to the substrate under test with an ion content less than a preset threshold is determined as the photoresist layer thickness that has passed safety verification; and the minimum value among the photoresist layer thicknesses that have passed safety verification is selected as the photoresist layer thickness for the ion implantation process. The step of measuring the ion content on the surface of each substrate to be tested includes the following sub-steps: A sacrificial layer is formed on the surface of the substrate under test after the photoresist layer is removed; the sacrificial layer is configured as an oxide layer, which is formed on the surface of the substrate under test after the photoresist layer is removed by an oxidation process, and forms an ion trapping layer through the oxide layer, chemically adsorbing ions that penetrate the photoresist layer on its surface; The sacrificial layer is completely or partially removed from the surface of the substrate under test and the sacrificial layer is collected. In this step, the oxide layer on the surface of the substrate under test is removed by etching with hydrofluoric acid vapor in a closed reaction chamber, and the droplets formed on the surface of the substrate under test are collected after the etching is completed. The ion content in the collected sacrificial layer was analyzed by inductively coupled plasma mass spectrometry and used as the ion content on the surface of the substrate to be tested.
Citation Information
Patent Citations
Method for monitoring stability and uniformity of ion implanter
CN103904009A
Ion implantation monitoring method
CN104091767A
Method for detecting ion implantation blocking capability of light resistor
CN120613283A
Semiconductor substrate and method of manufacturing thereof, semiconductor device and method of manufacturing thereof
JP2007173328A
Methods of forming SOI substrates
US20190088466A1
